Optimalisasi Wisata Desa Semanu Gunung Kidul melalui Media Digital Berbasis Website - Septian Rahman Hakim; Aris Nasuha; Dessy Irmawati; Moh Alif Hidayat Sofyan; Ahmad Taufiq Musaddid (Dharma Vritta Vokasional, 2025)
Limited access to information in Semanu Village, Gunungkidul Regency, Yogyakarta Special Region, has prevented the promotion of tourist destinations from reaching its full potential. The use of digital technology, particularly websites, was chosen as a solution to expand the dissemination of information. Through the website, the community can access and share information more conveniently. This community service activity focused on developing a web-based information system and transferring knowledge so that village officials could manage it independently. The website serves as a medium for publishing information on village tourist attractions and as a tool for promoting tourism potential quickly and accurately. The technology used is WordPress CMS with a MySQL database, and the site is hosted so that it can be accessed at any time. The implementation of the community service program includes two main activities: application development for three months and training on website utilization at the village office. The implementation of this website has proven to increase the visibility of local potential and encourage community involvement. The training ran smoothly and received positive responses from participants, including hamlet heads and managers, who now realize that the website not only serves as an information provider but also as a promotional medium. This activity also motivated village managers to be more active in managing and disseminating the village's tourism potential.